Genetic Diversity and Population Structure of Doum Palm (Hyphaene compressa) Using Genotyping by Sequencing - Omire, Agnes; Neondo, Johnstone; Budambula, Nancy L. M.; Wangai, Laura; Ogada, Stephen; Mweu, Cecilia (Frontiers in Genetics, 2022)
Doum palm (Hyphaene compressa) is a perennial economic plant primarily growing in Kenya's Arid and Semi-Arid Lands (ASALs). It is heavily relied upon for food, animal feed, construction materials and medicine, making it an ideal plant for resource sustainability. However, the limited information on its genetic resources has hindered its breeding and conservation studies. This study used the genotyping by sequencing approach to identify Single Nucleotide Polymorphisms (SNPs). These SNPs were further used to assess the genetic diversity and population structure of 96 H. compressa accessions from Coastal, Northern and Eastern ASAL regions of Kenya using two approaches; reference-based and de novo-based assemblies. STRUCTURE analysis grouped the sampled accessions into two genetic clusters (Cluster 1 and Cluster 2). Cluster 1 included all accessions from Eastern and Coastal regions, whereas Cluster 2 included only accessions from the Northern region. Accessions from Kwale (Coastal) had mixed ancestry from both Cluster 1 and Cluster 2. These STRUCTURE findings were further supported by principal components analysis, discriminant analysis of principal components and phylogenetic analysis. Analysis of molecular variance indicated greater genetic variation within populations (92.7%) than among populations (7.3%). An overall FST of 0.074 was observed, signifying moderate genetic differentiation among populations. The results of this study will provide information useful in breeding, marker-assisted selection and conservation management of H. compressa.